Job Satisfaction of TPK Group Yogyakarta Employees: Organizational and Industrial Psychology Perspectives - Yainahu, Hairani; Damayanti, Devi (Universitas Muhammadiyah Metro, 2020)
The purpose of this study was to see an overview of the level of job satisfaction of TPK Group employees in general from nine aspects; salary, promotion, supervision, benefits, rewards, operational procedures, co-workers, nature of work, and communication. This research is also to see aspects that affect job satisfaction and aspects that do not affect job satisfaction. The research method used is descriptive quantitative as a primary data collection tool and is supported by interviews. The subjects of this study were 43 employees of TPK Group Yogyakarta. The results showed that out of 43 employees, 16% (7 employees) had a high level of job satisfaction, 65% (28 employees) had a moderate job satisfaction level, and 19% (8 employees) had a low job satisfaction level. The supervision aspect has the highest effect value on job satisfaction, while allowances, operational procedures, and promotions get the lowest score related to employee job satisfaction at PT TPK Group. From the results of this study, it is suggested that companies/leaders need to conduct evaluations to improve systems and human resources so that the goals of the company can be achieved and improved.